Unveiling the Research Void: A Bibliometric Study on Digital Leadership in Immigration - Agus Widodo; Sudarmo; Rutiana Dwi Wahyunengseh (Journal of Law, Politic and Humanities, 2025)
Digital leadership is growing as technological advancements equip leaders with new features to tackle challenges in the digital era. This study aims to analyze the research trend of digital leadership to discover opportunities for future research in government organizations, especially in the context of the immigration sector, due to technology adoption to carry out its functions. This study utilized bibliometric analysis to analyze research publications from the Scopus database and create as well as visualize maps based on network data using VOSviewer software. Three hundred and sixty-six (366) documents were taken with the keyword “digital leadership”. The results showed that the early discussion of digital leadership started in 2015 and significantly increased in 2024. Indonesia contributed the most research compared to other countries. This study was mostly affiliated with Bina Nusantara University and mainly written by Abbu, H. The visualization result showed this study connected to five clusters focusing on gendered leadership, e-leadership in education, digital innovations and sustainability, artificial intelligence (AI) and digital learning, and digital transformation and capabilities. The absence of public organization cluster, especially in the immigration sector, implies that this study gives opportunities to guide future research among scholars and practitioners